Hidden hunger: Approaches to tackling micronutrient deficiencies - Hodge, Judith (International Food Policy Research Institute, 2016)
AROUND THE WORLD, more than 2 billion people are thought to be affected by an often invisible form of malnutrition: micronutrient malnutrition, commonly known as hidden hunger.1 Vitamin and mineral deficiencies—at least in mild to moderate forms—may not be as observable as wasting or obesity, but their effects are far-reaching. Globally, vitamin A deficiency (VAD) is the leading cause of blindness in children.2 Iodine deficiency causes 18 million babies to be born mentally impaired each year.3 And severe anemia caused by lack of iron is associated with the deaths of 115,000 women annually during childbirth.4 Vitamin A, iodine, and iron are classified as “the big three,” but deficiencies of other micronutrients, such as folate, zinc, vitamin B12, and vitamin D, are also important.